NAFKAH PASCA PERCERAIAN DALAM PERKARA CERAI GUGAT (STUDI KRITIK PADA PASAL 149 KHI TERHADAP PERKARA NOMOR 1145/Pdt.G/2010 P.A JS) - Irawan, Heri; Wagianto, M; Indra, Gandhi Liyorba (UAS PRESS, 2025)
This study aims to analyze the legal basis for the judge's considerations in deciding the case 1145/Pdt.G/2012/PA JS according to the Law and then will be analyzed using Islamic law against the judge's considerations in deciding the case 1145/Pdt.G/2012/PA JS. This study is a type of library research, this study is descriptive analytical, the primary data in this study is Law Number 1 of 1974 concerning marriage and the Compilation of Islamic Law. Using the Maslahah Mursalah Theory, data analysis in this study uses deductive thinking techniques, then the author makes data analysis with qualitative analysis. The results of the study are that the judge's considerations in deciding the case 1145/Pdt, G/2012/PA JS are Law Number 1 of 1974 Article 41 letter (c) which reads: the consequences of a marriage breaking up due to divorce are that the court can require the ex-husband to provide living expenses and/or determine an obligation for the ex-wife. The regulation in Article 149 letter (b) of the KHI only mentions the obligation of the ex-husband to provide iddah, kiswah, mut'ah and hadanah costs for his children after a divorce due to talak. Textually, divorce in the Article contains the meaning of divorce in general, so it can be interpreted that the religious court has the right to require the ex-husband to provide living costs and determine an obligation for the ex-wife due to divorce due to talak or due to a lawsuit. The analysis of Islamic law on the provision of living costs according to maslahah al-mursalah is to provide iddah, kiswah, and mut'ah living costs according to his ability as long as the wife who filed for a lawsuit divorce is not nusyuz, then as long as she has the right to receive living costs as a consolation and guarantor of her life for her own benefit so as to lighten the burden of her life. This aims to maintain the soul (al-nafs) of the ex-wife so that she gets benefit and aims to reject harm. This is in accordance with the theory of maslahah murlah, namely creating good benefits in social life, the household and even after divorce and rejecting all harm which ultimately makes the order damaged so that someone is harmed.